Th2-TRMs Maintain Life-Long Allergic Memory in Experimental Asthma in Mice - Bošnjak, Berislav; Kazemi, Sahar; Altenburger, Lukas M.; Mokrović, Gordana; Epstein, Michelle M. (Frontiers in Immunology, 2019)
Allergic asthma is a chronic inflammatory remitting-relapsing disease affecting the airways. Long-lived allergen-specific memory CD4+ T helper 2 (Th2) cells in mice persist in lungs for more than 2 years after the induction of experimental allergic asthma (EAA). To further understand lung Th2 memory cells, we tracked CD4+ T cells in spleen and lungs from healthy mice, through the initiation of acute EAA, recovery (remission), and allergen-induced disease relapse. We identified a lung CD3+CD4+ cell subset that expresses CD44hiCD62L-CD69+ST2+, produces Th2 cytokines, and mediates allergen-induced disease relapse despite treatment with FTY720 and anti-CD4 antibody. These cells reside in the lung tissue for the lifetime of mice (>665 days) and represent long-lived pathogenic Th2 tissue resident memory cells (TRMs) that maintain ‘allergic memory’ in lung. We speculate that these data implicate that human Th2-TRMs sentinels in lungs of patients are poised to rapidly respond to inhaled allergen and induce asthma attacks and that therapeutic approaches targeting these cells may provide relief to patients with allergic asthma.